PONM11 "The eyes have it": initial genetic screening in suspected congenital myasthenia. Issue 11 (22nd October 2010) - Lashley, D; Burke, G; Beeson, D; Palace, J
Abstract : The congenital myasthenic syndromes (CMS) are a heterogenous group of inheritable disorders of neuromuscular transmission. Screening each of the eight genes thus far identified as commonly causing CMS in every suspected patient would be inefficient. We propose a strategy for targeted initial screening, based on the ophthalmoplegia present. The four most common syndromes (see Abstract PONM11 Table 1 ) account for 85% of genetically confirmed CMS and from our clinical database the presence of ophthalmoplegia and the mean fractional range of movement (ROM, 0 to 1) are: In those patients with ophthalmoplegia screening should begin with the AChR subunits, starting with CHRNE. For patients without ophthalmoplegia the RAPSN and DOK7 genes should be initially screened. This screening strategy without using other specific guiding features (e.g., pattern of weakness, presence of arthrogryposis and squint, response to treatment, childhood apnoeas, double response on electromyography) would identify the causative mutation in 88% of the individuals included in this study. Further refinements using the severity of the ophthalmoplegia may improve the screening process.